2015
DOI: 10.3109/13668250.2015.1014323
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the ADEC as a Level 2 screening test for young children with suspected autism spectrum disorders in a clinical setting

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Experts missed 39% of children with ASD when asked whether they would refer the child for an evaluation after each 10-min sample, indicating that this rating tool is not effective in detecting risk for ASD in toddlers in a brief observation during a semi-structured interaction. Additional brief observational screening measures have been developed, including the Autism Detection in Early Childhood (ADEC; Dix et al, 2015) and the Rapid Interactive Test for Autism in Toddlers (RITA-T; Choueiri and Wagner, 2015), though further research with larger samples is needed to evaluate their potential utility. Despite the potential benefit of using level-two detection methods to determine early risk for ASD, adequate measures are not currently available for toddlers within the recommended screening age.…”
mentioning
confidence: 99%
“…Experts missed 39% of children with ASD when asked whether they would refer the child for an evaluation after each 10-min sample, indicating that this rating tool is not effective in detecting risk for ASD in toddlers in a brief observation during a semi-structured interaction. Additional brief observational screening measures have been developed, including the Autism Detection in Early Childhood (ADEC; Dix et al, 2015) and the Rapid Interactive Test for Autism in Toddlers (RITA-T; Choueiri and Wagner, 2015), though further research with larger samples is needed to evaluate their potential utility. Despite the potential benefit of using level-two detection methods to determine early risk for ASD, adequate measures are not currently available for toddlers within the recommended screening age.…”
mentioning
confidence: 99%
“…The last study that we found was by Dix, Fallows, and Murphy (). They used a retrospective file audit to investigate the clinical effectiveness of the ADEC as a Level 2 autism screening tool in a community setting.…”
Section: A Review Of Studies Examining the Adec’s Effectiveness In Eamentioning
confidence: 84%
“…The child is scored on each behavior from 0 (appropriate) to 2 (inappropriate), allowing a maximum score of 32. Several converging validity assessments have been reported (Dix et al, 2015; Hedley et al, 2015; Nah, Young, & Brewer, 2014; Nah, Young, Brewer, & Berlingeri, 2014).…”
Section: Methodsmentioning
confidence: 99%